Perubahan Harga, Volume Saham, dan Kapitalisasi Pasar Selama COVID-19 pada Sektor Keuangan - Joanna Yutanesy; Rousilita Suhendah (Jurnal Ekonomi, 2022)
The purpose of this study is to analyze about the difference of stock prices, stock trading volume, and market capitalization before and during the COVID-19 outbreak on the financial sector listed on the Indonesia Stock Exchange during January 1, 2020 until April 30, 2020 period. The research design is a descriptive study and double regression. This study used a purposive sampling method, which is a non probability sampling, amounted to 100 financial companies. The hypothesis testing is done by Wilcoxon signed rank test, a non parametric statistic test. This study used SPSS 26th versions software. The result shows that there is a significant negative difference of stock price, stock trading volume, and market capitalization before and during the COVID-19 outbreak on the financial sector. Furthermore, this study shows that there is no significant difference of stock trading volume before and during the COVID-19 outbreak on the financial institution subsector.